Gambaran Self Control Siswa yang Berperilaku Merokok di SMP - Julia, Azmi Sri Wahyu; Nurfarhanah, Nurfarhanah (Asian Journal of Islamic Studies and Da'wah, 2024)
This research was motivated by the existence of students who smoked in junior high school. Even though there is no direct impact on teaching and learning activities, this smoking behavior needs to be given special attention because students at the junior high school level have the potential to become addicted to consuming cigarettes. Therefore, students are expected to be able to control themselves. Self control is an individual's ability to control and regulate their behavior, emotions and desires with the aim of achieving desired results. The aims of this research are (1) to describe the self-control of students who smoke in junior high school from the behavioral control aspect, (2) to describe the self-control of students who smoke in junior high school from the cognitive control aspect and (3) to describe the self-control of students who smoke in junior high school. from the aspect of decisional control. This research uses a descriptive quantitative approach. The population and sample in this study were male students in grades VII, VIII and IX in junior high school who had a tendency to smoke as many as 85 students. Determination of the sample in this research was total sampling. The instrument used in this research is a self-control instrument with a Likert model scale. The data analysis technique used is descriptive analysis. Based on the results of this research, it shows that (1) student self control seen from the behavior control aspect is in the high category with a percentage of 35.29%, (2) student self control seen from the cognitive control aspect is in the medium category with a percentage of 36.47% and (3) student self-control seen from the aspect of decisional control is in the low category with a percentage of 37.65%.